2016
DOI: 10.1177/1744629516650129
|View full text |Cite
|
Sign up to set email alerts
|

Fathers of people with intellectual disability: A review of the literature

Abstract: The aim of this article is to review the literature related to fathers of people who have an intellectual disability (ID). Electronic databases and citation tracking were used to collate data using key terms such as fathers, adults with an ID, learning disability, mental handicap and developmental disability. Relevant articles were analysed and compared for commonality and difference. Eight themes emerged from the literature: response to diagnosis, varied response to ID, concern for the future, work, roles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
3
46
1
3
Order By: Relevance
“…This emotional downturn is also consistent with Davys et al. () systematic literature review in which fathers of children with intellectual disabilities reported high levels of emotional intensity, shock, fear and stress at the time of diagnosis of a child’s intellectual disability. Findings from the current study further provide support that fathers prepare for and anticipate the birth of a nondisabled child irrespective of whether it is a first or subsequent child.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This emotional downturn is also consistent with Davys et al. () systematic literature review in which fathers of children with intellectual disabilities reported high levels of emotional intensity, shock, fear and stress at the time of diagnosis of a child’s intellectual disability. Findings from the current study further provide support that fathers prepare for and anticipate the birth of a nondisabled child irrespective of whether it is a first or subsequent child.…”
Section: Discussionsupporting
confidence: 89%
“…This Irish study extends the knowledge of fathers’ experiences within the context of leading up to the diagnosis and the actual diagnosis of a child’s intellectual disability. Regardless of the timing of the diagnosis, all fathers experienced an emotional downturn, a view supported throughout the literature (Bourke et al., ; Davys et al., ; Huang et al., ; Takataya et al., ; Waite‐Jones & Madill, ). While fathers are affected by the diagnosis of a child’s intellectual disability, healthcare professionals must recognise and respond to their distinct and individual needs at this critical diagnostic period.…”
Section: Discussionmentioning
confidence: 68%
“…The present study had a number of novel features. Fathers as well as mothers were recruited, and the scarcity of information about fathers is globally recognized [17]. Our findings suggest that Iranian fathers report similar patterns of satisfaction and stress as mothers do, which is contrary to some studies in Western countries [18] but confirms the findings from previous studies undertaken in Iran [14].…”
Section: Discussionsupporting
confidence: 60%
“…Achieving a balance between work and family life may be more difficult when raising a child with ID due to additional caring responsibilities. There is evidence to suggest that raising a child with ID can have an impact upon work but also that work can impact upon a father's ability to care for their child (Davys et al, ). Couples tend to become more differentiated in their work and family roles when they become parents, with men more likely to be the main breadwinner (Katz‐Wise et al, ).…”
Section: Introductionmentioning
confidence: 99%